Receptor-mediated signaling in Aspergillus fumigatus - Grice, C. M.; Bertuzzi, M.; Bignell, E. M. (Frontiers in Microbiology, 2013)
Aspergillus fumigatus is the most pathogenic species among the Aspergilli, and the major fungal agent of human pulmonary infection. To prosper in diverse ecological niches, Aspergilli have evolved numerous mechanisms for adaptive gene regulation, some of which are also crucial for mammalian infection. Among the molecules which govern such responses, integral membrane receptors are thought to be the most amenable to therapeutic modulation. This is due to the localisation of these molecular sensors at the periphery of the fungal cell, and to the prevalence of small molecules and licensed drugs which target receptor-mediated signalling in higher eukaryotic cells. In this review we highlight the progress made in characterising receptor-mediated environmental adaptation in A. fumigatus and its relevance for pathogenicity in mammals. By presenting a first genomic survey of integral membrane proteins in this organism, we highlight an abundance of putative 7TMD receptors, the majority of which remain uncharacterised. Given the dependency of A. fumigatus upon stress adaptation for colonisation and infection of mammalian hosts, and the merits of targeting receptor-mediated signalling as an antifungal strategy, a closer scrutiny of sensory perception and signal transduction in this organism is warranted.